(untitled) (Research, Society and Development, 2022)
Kissing Molars is a term used to describe impacted teeth that contact occlusal surfaces in a single follicular space. The occurrence of this phenomenon is extremely rare and of unknown etiology. Therefore, the present study aimed to present a case report of Kissing Molars associated with dentigerous cyst where a surgical procedure was needed under general anesthesia due to the atrophied jaw. On the left side, of the mandible, and fracture after the removal of the impacted teeth happened and a 2.4 mm reconstruction plate was installed. After the extraction of impacted molars, the lesion with a cystic aspect was removed and sent to histopathological analysis which confirmed the diagnostic hypothesis of dentigerous cyst. Thus, it was concluded that despite the rare impaction and unknown etiology, with a little report in the literature, clinically the case behaves like any impacted tooth, and inflammation may occur if it partially erupts. Radiographically, it presents with the occlusal surfaces in contact and a single follicle, usually associated with the dentigerous cyst.